Study of incidence of hypocalcaemia in patients undergoing total thyroidectomy for papillary carcinoma: a retrospective study - Gayathre, S. P.; Kumar, R. Niranjan; Prabu, M. J. (International Surgery Journal, 2021)
Background: Hypocalcaemia following total thyroidectomy is a fairly common complication. Occurrence of acute hypocalcaemia can be predicted in patients undergoing thyroid surgery for malignancy, based on serial calcium measurement and this helps in early prediction of hypocalcaemia. The aim of the study was to assess the incidence of post thyroidectomy hypocalcaemia and methods to treat hypocalcaemia and prevention of its complication at the earliest. Methods: The incidence of hypocalcemia was analysed with serial calcium estimation in immediate post-operative period, 4 hours and 24 hours after surgery and on 5th post-operative day. The factors analysed included pre-operative and post-operative serum calcium levels, clinical features, the disease type and factors related to surgery and histopathologically diagnosis as malignant papillary thyroid carcinoma is confirmed. Results: In this study 30 patients underwent total thyroidectomy for papillary carcinoma were studied. Incidence of 22% of hypocalcemia, with transient hypocalcemia in 20% and permanent hypocalcemia in 2% of cases were noted. Conclusions: Patients underwent thyroid surgery for malignant conditions showed higher incidence and severity hypocalcaemia. This complication can be prevented with meticulous peroperative dissection, prompt identification of parathyroid gland. Avoiding injury or spasm of the blood vessels supplying them and frequent postoperative monitoring of serum calcium levels.